WAQF DEEDS OF THE SHAYBANID DYNASTY AND THEIR HISTORICAL - ECONOMIC SIGNIFICANCE (Modern American Journal of Social Sciences and Humanities, 2025)
This scholarly article examines the impact of the decisions of the 26th Party Congress and other significant party documents on the development of Soviet historiography. It explores how these decisions guided Soviet historians toward the study of contemporary society, influenced historical methodology, and shaped the overall trajectory of historiographical research. By analyzing these party directives, the article highlights the methodological importance of political guidelines in historical investigations and demonstrates their enduring influence on modern historical scholarship. Furthermore, the study contextualizes the evolving trends in Soviet historiography and provides critical insight into the interplay between political directives and historical analysis.